Pembelajaran Materi Perkalian Dasar dengan Menggunakan Metode Menghadirkan Matematika dalam Kehidupan Peserta Didik (MMDKP) - Firmansyah, Muhamad Taufiq (Prodi PGMI STAI At-Tahdzib Ngoro Jombang, 2024)
The aim of writing this paper is to describe the application of the method of presenting mathematics in students' lives (MMDKP) for learning basic multiplication for grade 2 students. This MMDKP method departs from the learning theory put forward by Dienes. Dienes views mathematics as investigating structures, classifying structures, sorting out structural relationships. Dienes believes that every mathematical concept or principle can be understood correctly if the concepts or principles are presented through various concrete and varied representations. The MMDKP method aims to attract students' interest in mathematics. Because if you use the MMDKP method, there are steps that must be followed so that students do not have difficulty understanding the mathematical concepts that will be taught. These steps start from something concrete (real objects) then proceed to semi-concrete (real objects are replaced with images) and finally abstract (only in the form of numbers and symbols). This can reduce a view of mathematics that was initially very abstract to a less abstract level.